A Comparative Analysis of Steam Distillation and Enfleurage Methods for the Extraction of Cananga odorata Flower Essential Oil - Elisa, Elisa; Muslikh, Faisal Akhmal; Dewi, Tanaya Jati Dharma; Ma’arif, Burhan (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2483, 2023)
Essential oils are made from the natural extracts of many different kinds of plants. Indonesia has a lot of potential for making essential oils that could make it the leader in the essential oil market around the world. One of them is the essential oil from the Cananga odorata flower, which is used a lot in the pharmaceutical industry and others. The aim of this research was to compare methods of extracting essential oils from C. odorata leaves that can produce oils of good quality and that meet standards. In this study, steam distillation and enfleuration methods were used to extract the essential oil from the flower. Essential oil extracted with steam distillation had a yield value of 1.87%. Its characteristics were that it was light yellow in color, had a distinct fragrance, had a refractive index of 1.480, and had a specific gravity of 0.908 g/mL. The yield of essential oil from enfleurage was 2.87%, and it was dark yellow with a distinct fragrance. It had a refractive index of 1.510 and a specific gravity of 0.9012 g/mL. The GC-MS analysis of the essential oil from the steam distillation found 21 different compounds. The highest of these was b-cubebene (19.92%). The GC-MS analysis of the essential oil from enfleuration method found 15 different compounds, with caryophyllene (39.94%) being the highest. Based on the findings, it was concluded that the enfleuration method was more optimal for extracting essential oils from C. odorata.